A novel intra-oral lubricating device for dry mouth patients / Lim Tong Wah … [et al.] - Lim, Tong Wah; Banerjee, Avijit; Cook, Richard; Fenlon, Michael (Research Innovation Business Unit, 2014)
The treatment available currently for severe xerostomia are non-specific and based principally on symptomatic relief as most of the causes of this condition are difficult to cure or eliminate. At present, clinical management relies primarily on self-administered topical saliva substitutes, saliva stimulants and systemic agents which are only applicable during waking hours. However, as the salivary flow rate drops significantly during sleep, most patients experience the worst dryness symptoms at night and sleep is disturbed regularly. Objectives: to develop a system which is suitable to form the basis of in-vivo clinical trials on patients who have extreme needs for salivary enhancement, aiming to improve their oral health status and quality of life. Methodology: an oral splint prototype was developed using soft/ hard two layers ethylene vinyl acetate. The prototype included silicone tubing which was used to transfer the lubricating agent from an extracorporeal reservoir - baxter ap ii patient-controlled analgesia pump to the oral splint to deliver the lubricant intra-orally at night. Outcomes: the design of intra-oral lubricating device might be suitable to form the basis of in-vivo clinical trials on xerostomic patients. It also represents a concept for the versatility of the device in which various drugs can be administered via this system.